Sistemas “partidocráticos” en crisis. Los casos de Perú e Italia - González Manrique, Luis Esteban (1995)
The political processes of Peru and Italy share similar trails: the currently irrelevant old political groups that held sway for most of the century in Peru and the collapse of Italy's 'partltocracy'. The emerging of a two-party system in Peruvian politics is the consequence of the need to move on from the old system. Moreover, the end of the first Italian Republic includes the abolition of a system founded on the political Catholicism, socialism and communism. Free market rules have been adopted in both processes as a cleaning instrument of the populist corporatism. Some reforms are required in order to free the economy from excessive political intervention as well as to redefine the government's role. In conclusion, this article presents a legitimacy crisis in the establishment. This situation is reflected in the emergence of new groups without traditional ideologies, whose aim is to eliminate oligarchic trends from democracy.